Normative values for heart rate response to exercise in young athletes at 10-18 years old - Mascherini, G.; Galanti, G.; Stefani, L.; Izzicupo, P. (European Journal of Sport Science, 2023)
The assessment of the chronotropic response during acute physical exertion can allow the discovery of many cardiovascular diseases even at a young age. However, the increase in heart rate (HR) depends on the age and sex of the subject and the modality of the graded exercise test. This study aims to provide sex- and age-related normative values for heart rate performance in young athletes aged 10-18. A retrospective study was carried out on 7896 young athletes (5356 males and 2540 females) aged between 10 and 18 who underwent pre-participation screening to obtain eligibility for competitive sport. First, anthropometric parameters, performance data, and HR are reported. Thus, each age calculated third, tenth, twenty-fifth, fiftieth, seventy-fifth, ninetieth, and ninety-seventh percentiles for the stage-by-stage HR response, according to sex and graded exercise test modality category. Young female athletes of all ages showed lower performance with fewer stages performed on the cycle ergometer and the treadmill. Young male athletes on treadmill and cycle ergometers show lower HR values at submaximal intensities. The treadmill allows a longer duration than the cycle ergometer for males and females. Sex, age, and the specificity of the movement performed must be considered in assessing the chronotropic response in the young population, particularly for those who carry out a training program. In addition, providing reference values of HR response to acute physical exertion may allow for a better functional assessment of the young athletes.